Proposta de estruturação de um modelo de gestão com base na logística reversa sustentável para os resíduos eletroeletrônicos em Aracaju/Sergipe/Brasil - Cruz, Izaclaudia Santana da (2016)
Brazil's National Solid Waste Policy establishes the obligation of reverse logistics for electrical and electronic waste (WEEE), which currently represent a considerable percentage of the total solid waste generated. Proper recycling of WEEE is crucial because it has high harmful potential to pollute the environment and to cause health problems, and it has a significant residual economic value. Thus, it is evident the need for advances in research to present solutions for the management of electronic waste within the municipalities. The overall objective of this study was to propose a management plan for electronic waste for the city of Aracaju/Sergipe, aligned with post-consumer takeback logistics, according to the Law 12,305 of 02 August 2010. The research was characterized as descriptive and exploratory, consisting of the following steps: in-depth study of publications on the subject; characterization of the current situation of electronic waste in the municipality of Aracaju/Sergipe, through interviews and field research on recycling and technical assistance; development of a takeback plan for electronic waste for this municipality, based on similar Brazilian and overseas takeback models. The results of this study contribute to solve the problem of this type of waste in the city of Aracaju, as well as to support public policies and other projects on the theme "solid waste management and environmental sustainability."